A Case of Hepatotoxicity Induced by Therapeutic Ketamine Use for Sedation - Noah Yoo; Sarun Thomas; Michael Bender; Xian Jie Cindy Cheng (Case Reports in Critical Care)
Ketamine, initially developed as an anesthetic, has shown versatility in medical applications, including pain management, treatment-resistant depression, and sedation in the intensive care unit (ICU). While generally well-tolerated, long-term use at high doses raises concerns about potential toxicities, particularly in the liver. We present a case of a 27-year-old female with a complex medical history who received ketamine infusion for ICU sedation and experienced a sudden rise in liver function tests (LFTs), indicating possible ketamine-induced liver injury (KILI). The patient’s liver function normalized after ketamine discontinuation. KILI is infrequent with short-term ketamine use, but emerging case reports suggest it may be associated with chronic or intermittent exposure. The underlying mechanisms for KILI are not fully understood but may involve the accumulation of ketamine metabolites, causing direct toxic effects on the liver. As ketamine’s use expands, especially in critical care settings, clinicians should be vigilant for the potential development of KILI. Further research is needed to better understand its risk factors and mechanisms, as early detection and management of KILI are crucial to ensuring patient safety and optimizing ketamine’s therapeutic benefits.